Production of natural protein using chicken feather - Ramanan, Perumal (2010)
A research was conducted on producing protein from chicken feathers. Protein is an important nutrient needed by our body to maintain body structures and important ingredient for cosmetic products. Chicken feathers have elevated keratin protein content and can be a suitable protein source. The main processes are dissolving chicken feathers and separation of proteins. Reducing agents Potassium cyanide, thioglycolic acid and sodium sulfide used for the dissolving process. Ammonium sulfate is used for the separation process. Once the feathers are dissolved ammonium sulfate solution is added to the solution which will precipitate protein. The precipitated protein is washed with water and dissolved in sodium hydroxide solution to obtain protein solution. Sodium sulfide has the highest efficiency in dissolving chicken feathers since the feathers are dissolved in a very short period of time. After the methods of precipitation, washing and dissolving the protein solution obtained is confirmed as pure protein solution by biuret test. An analysis by the Ftir confirmed the presence of carboxyl acid and amino groups only. Thus the sample obtained is true protein since the presence of functional groups is proven. From this research can be concluded that protein can be produced from chicken feathers. Hopefully chicken feathers will be used as a source of protein production in a bigger scale in the future.